2009
DOI: 10.1111/j.1365-2591.2009.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain associated with root canal treatment

Abstract: Root canal treatment in teeth with irreversible pulpitis and acute apical periodontitis was more painful. Age, tooth type and length of the treatment were factors associated with increased risk for pain experienced during the procedure. Knowledge of pain levels endured by patients will allow dentists to decide when to use supplemental local anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(129 citation statements)
references
References 24 publications
13
99
2
8
Order By: Relevance
“…When considering arch group and type of teeth, pain is experienced more in mandibular group and pre-molar teeth than maxillary and anterior teeth at both 1 st and 7 th post obturation days (Table 2 & In 1 st post obturation day as well as 7 th post obturation day females reported more pain than males. These results support findings of previous workers 16,17,22,23,24,25,26 . Female patients experienced more pain than male patients, a possible explanation is that biological differences between genders may explain increased pain prevalence in females 17 .…”
Section: Methodssupporting
confidence: 83%
“…When considering arch group and type of teeth, pain is experienced more in mandibular group and pre-molar teeth than maxillary and anterior teeth at both 1 st and 7 th post obturation days (Table 2 & In 1 st post obturation day as well as 7 th post obturation day females reported more pain than males. These results support findings of previous workers 16,17,22,23,24,25,26 . Female patients experienced more pain than male patients, a possible explanation is that biological differences between genders may explain increased pain prevalence in females 17 .…”
Section: Methodssupporting
confidence: 83%
“…A study has shown that a higher number of male patients feel pain during dental treatment as compared to females 6 . However, a different study has not shown significant differences between genders, although females had a higher incidence of pain 9 . It seems that the higher is the level of education of patients, the higher is pain intensity report, but marital status is not associated to pain awareness 6 .…”
Section: Influence Of Sociodemographic Cha-racteristics Of Patients Omentioning
confidence: 81%
“…This does not mean that pain is not present in noninvasive procedures, because 25% of a sample of young adults submitted to procedures such as probing, prophilaxy and removal of supragingival calculus have reported severe pain at some moment 8 . The risk of feeling pain during endodontic treatment is higher for irreversible pulpitis or acute apical periodontitis as compared to chronic lesions, as well as for posterior teeth treatment with longer sessions 9 . To minimize or prevent pain during dental procedures, local or regional anesthesia is induced.…”
Section: Painful Dental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Além disso, a situação clínica descrita acima, aliada à idade acima de 40 anos, revela a perda da inervação dentinária e do suprimento vascular e nervoso da polpa dentária, resultado da calcificação dos vasos e das terminações nervosas, o que se traduz por uma diminuição da excitabilidade do dente, provocando alterações nas respostas aos testes de vitalidade pulpar 7 . Alguns autores observaram em seus estudos que jovens e adultos sentem mais dor que idosos, já outros verificaram que a probabilidade de sentir dor era menor para os indivíduos acima de 35 anos do que para os mais jovens 11,12 . Em outro estudo foi observado que a dor frequentemente está associada com o cuidado com os dentes, de modo que mais de 60% dos pacientes odontológicos relatam alguma dor durante suas visitas ao dentista 13 .…”
Section: Discussionunclassified